Long-term three-dimensional skeletal effects of hybrid hyrax with facemask versus mentoplate in growing Class III patients: a randomized controlled trial - Joeri Meyns; Jindanil Thanatchaporn; Sohaib Shujaat; Constantinus Politis; Reinhilde Jacobs (Progress in Orthodontics)
Abstract Background Early intervention in Class III malocclusion aims to prevent the need for surgery in adulthood by enhancing upper jaw growth while limiting lower jaw development. Although traditional facemask treatment remain common, bone-anchored devices are increasingly used, claiming better skeletal control and patient compliance. However, strong evidence supporting these advantages is limited. Methods Single-center, parallel-group, randomized controlled trial with 1:1 allocation ratio. Participants: 28 growing Class III patients (mean age 9.7 ± 1.3 years) in mixed dentition with skeletal class III malocclusion. Interventions: Patients were randomly assigned to either hybrid hyrax with facemask (HH + FM, n = 14) or hybrid hyrax with mentoplate (HH + MP, n = 14). All received Alt-RAMEC protocol expansion. FM group used 360–400 g/side elastic traction 12–14 h daily; MP group used 185 g/side continuous traction. Objective: To compare 5-year three-dimensional (3D) skeletal effects between HH + FM and HH + MP protocols. Outcome: Primary outcome was 3D volumetric changes of upper and lower jaw at 1 year (T1) and 5 years (T2) post-treatment, measured using low-dose CT scans. Randomization: 28 patients were allocated to either treatment-protocols using sequentially numbered opaque, sealed envelopes. The randomization sequence was generated with a 1:1 allocation ratio. Blinding: Due to the nature of the trial, the operator and children could not be blinded to the treatment allocation. However, blinding was used when assessing the outcomes. Results Follow-up: one patient was lost at the one-year follow-up and an additional three patients were lost at the 5-year-follow-up. Outcomes: At T2 (5 years), maxillary advancement was identical between both groups (0.85 mm ± 0.5). Mandibular growth control showed minimal difference (FM: − 0.01 mm ± 0.24; MP: 0.10 mm ± 0.33). No significant differences were found between groups for any skeletal measurements (p > 0.05). Male patients showed lager mandibular changes both signed (p < 0.03) and unsigned (p < 0.01). Harms: minor harms were encountered with the anchor hooks (fracture or mucosal irritation), however none led to treatment cessation. Conclusions Both protocols demonstrated comparable long-term skeletal effects in Class III correction. Treatment choice should be based on individual patient factors rather than assumed mechanical advantages.